2016
DOI: 10.1155/2016/6817397
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cortical Representation and Structural Connectivity of Hands and Feet between Professional Handball Players and Ballet Dancers

Abstract: It is known that intensive training and expertise are associated with functional and structural neuroadaptations. Most studies, however, compared experts with nonexperts; hence it is, specifically for sports, unclear whether the neuroplastic adaptations reported are sport-specific or sport-general. Here we aimed at investigating sport-specific adaptations in professional handball players and ballet dancers by focusing on the primary motor and somatosensory grey matter (GM) representation of hands and feet usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 64 publications
2
37
0
2
Order By: Relevance
“…Apart from functional alterations, regular training is also capable of inducing changes on a structural brain level. Meier et al (2016) suggested that structural adaptations are even sport-specific and are manifested in brain regions which are essential for neural processing of sport-specific skills. They found an increased gray matter (GM) volume in the hand area of M1 of handball players as compared to non-athletes, whereas ballet dancers showed an increased GM volume in the foot area of M1.…”
Section: Diagnostics Of Neuroplasticity Using Non-invasive Brain Imagmentioning
confidence: 99%
“…Apart from functional alterations, regular training is also capable of inducing changes on a structural brain level. Meier et al (2016) suggested that structural adaptations are even sport-specific and are manifested in brain regions which are essential for neural processing of sport-specific skills. They found an increased gray matter (GM) volume in the hand area of M1 of handball players as compared to non-athletes, whereas ballet dancers showed an increased GM volume in the foot area of M1.…”
Section: Diagnostics Of Neuroplasticity Using Non-invasive Brain Imagmentioning
confidence: 99%
“…In this context, a recent study of Moscatelli et al (2016) demonstrated greater corticospinal excitability in karate athletes with respect to controls, indicating a sport-specific adaptation between inhibitory and excitatory network in modulating the final command from M1. When comparing professional handball players and ballet dancers, Meier et al (2016) demonstrated neuroplastic adaptations in the gray matter (GM) representation and corticospinal path (CP) of the foot and the hand area depending on sport practice. GM volume and CP density were respectively more important in hand areas of handball experts and in foot areas of ballet dancers.…”
Section: The Electromyographic Signals (Emg) As a Prediction Of Flow mentioning
confidence: 99%
“…GM volume and CP density were respectively more important in hand areas of handball experts and in foot areas of ballet dancers. This sport-specific dependency of the corticospinal commands (Hänggi et al, 2010, 2015; Bar and DeSouza, 2016; Meier et al, 2016) should be taken into account in the flow state research.…”
Section: The Electromyographic Signals (Emg) As a Prediction Of Flow mentioning
confidence: 99%
“…Another important finding to note is that motor resonance is increased by a higher amount when experts in a sport observe a short sequence of movement that is common in their domain of expertise than when they observe a sequence of unusual activity. 16,17 Moreover, Meir et al 16 revealed that extensive practice in a specific sport can influence brain plasticity through the modification of the activities of the motor areas solicited by that sport. 18 Considering the above, the present study evaluates whether expertise in fighting-sports (e.g., taekwondo), in which facial recognition represents a strategic ability, produces better recognition of facial expressions than expertise in sports in which such ability is less important (e.g., soccer).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a soccer field has a minimum area of 4050 m 2 , in which SOC players are mainly required to follow the movement of the ball and the placement of teammates and opponents in order to be able to predict future actions; hence, they have few opportunities to directly read the facial expressions of their opponents. 19,34 In their study, Meier et al 16 suggest that structural adaptations are sport specific and are manifested in cerebral areas associated with the neuronal treatment of sport-specific-skills, which means that long-term sport practice can modulate cerebral plasticity in order to fit the specificities of the practiced sport.The concept of motor resonance is a complex one, and it has been proposed to occur without conscious effort nevertheless this does not mean that everyone resonates with just anyone in any situation. …”
mentioning
confidence: 99%